Is Alcohol Drinking Associated with Renal Impairment in the General Population of South Korea? - Ha-Na Kim; Se-Hong Kim; Sang-Wook Song (Karger Publishers, 2014)
Background/Aims: We examined relationships between the average amount of daily alcohol intake, drinking patterns, and renal dysfunction among South Korean adultsaged ≥ 20 years. Methods: The analysis used data from the Korean National Health and Nutrition Examination Survey (KNHANES), a cross-sectional survey of Korean civilians, conducted from January to December 2011. In this study, a sample of 5,251 participants was analysed. Results: Compared with abstinence, the odds ratio for a decrease in estimated glomerular filtration rate (eGFR) was 0.14 (95% CI: 0.01-0.91) among heavy drinkers, and 0.42 (95% CI: 0.17-0.98) among binge drinkers and the association between the amount of mean daily alcohol intake, binge-drinking status and a likelihood of reduced eGFR value showed significant trends (p = 0.041 and p = 0.038, respectively), after adjusting for age, smoking status, amount of physical activity, morbid hypertension, diabetes, dyslipidaemia, anaemia and body mass index. There was no significant association between alcohol consumption and the urine albumin to creatinine ratio in men, or between alcohol consumption and renal dysfunction in women. Conclusions: Alcohol consumption was inversely associated with a reduction in eGFR in Korean men. However, these findings should be interpreted cautiously, given the other harmful effects related to alcohol consumption, especially heavy and binge drinking.